Coastal gradients and human disturbance shape bacterial and fungal rhizosphere microbiomes of Heliotropium arboreum in Hainan, China - Zhang, Xiaofeng; Sha, Linhua; Mai, Youzhuan; Xu, Jianhui; Nizamani, Mir Muhammad; Fang, Fazhi (Frontiers in Microbiology, 2026)
Coastal ecosystems in Hainan exhibit steep sea–land gradients in salinity and nutrient availability, yet the rhizosphere microbiome of the pioneer shrub Heliotropium arboreum remains poorly understood. We investigated bacterial and fungal communities across seven coastal sites using replicated transects from seaward to shrub-belt to inland zones, and linked community patterns to soil physicochemical properties and human disturbance. Bacterial communities consistently showed higher richness, evenness, and compositional stability than fungal communities. Alpha diversity increased from seaward to inland zones for both groups, with a stronger gradient in fungi. Community composition was dominated by Proteobacteria and Planctomycetota in bacteria and Ascomycota in fungi, with distinct dominant genera across zones and sites. β-diversity analyses revealed clear differentiation of microbial communities among zones and locations, with fungi showing stronger turnover and site separation than bacteria, indicating higher sensitivity to environmental filtering and disturbance. Redundancy analysis indicated that fungal communities were primarily structured by available potassium, total nitrogen, and soil organic carbon, whereas bacterial communities were most strongly associated with soil pH (7.468–9.613 across sites) and nitrate concentrations. Functional profiling suggested complementary roles in decomposition and nitrogen cycling, and human-disturbed sites showed higher predicted pathogenic potential. Overall, H. arboreum hosts an environmentally filtered rhizosphere microbiome shaped jointly by coastal gradients and disturbance, with fungi responding more strongly than bacteria to spatial and environmental variation.